Costa Rica : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that Costa Rica's economic performance improved in 2003. Following several years of slow growth, real GDP rose by 5 1\2 percent, boosted by a recovery of exports and strong private investment. Inflation declined below 10 percent while unemployment fell to 6 percent. Real GDP is expected to expand by 4 percent in 2004, and while inflation has risen to 11 percent recently owing to higher oil prices, core inflation remains stable at about 10 percent, broadly in line with the rate of crawl.